Prevalence of low back pain in Latin America: A systematic literature review (2014)
Background: Chronic low back pain is considered as a high-impact condition that affects the working population of Latin America, with long reaching social and economic repercussions. Its true frequency is unknown due to the absence of well-designed clinical trials that use standardized definitions and criteria.Objectives: To evaluate the prevalence of chronic non-specific low back pain among the Latin American population.Study Design: A systematic review of chronic non-specific low back pain in Latin America.Setting: Meeting of Change Pain Latin America, Mexico.Methods: Data sources included relevant literature identified through searches of published studies between August 30, 2002, and August 30, 2012, in 7 electronic databases: Cochrane BVS, Pubmed, Medline, Lilacs, Scielo, Hinari, and MedCarib. Publications dealing with low back pain of a posttraumatic, infectious, or malignant origin were excluded. Two reviewers selected in an independent manner all eligible studies using the MOOSE checklist and extracted data on both prevalence and risk factors associated with low back pain. A narrative synthesis of the results was drafted, which was later validated by a panel of clinical experts on pain.Results: Twenty-eight studies were included in the review, comprising a total of 20,559 subjects from 7 countries in the region. Four of these studies, with significant methodological differences between them, measured the frequency of chronic low back pain with results that varied from 4.2% to 10.1%. Four studies are part of the Community Oriented Program for Control of Rheumatic Diseases (COPCORD) program reports, and were pooled and analyzed separately because of their particular design. Their prevalence estimations varied between 1.8% and 11.3%. The remaining 20 studies evaluated a total population of 6,992 subjects, and found a prevalence of low back pain of 31.3%. Based on an epidemiological model constructed on both times to resolution and low back pain recurrence rates, the prevalence of chronic low back pain in Latin America was estimated to be around 10.5%. Some risk factors reported by the authors are long working hours with the worker in the sitting position, obesity and overweight, pregnancy, smoking, advanced age, lifting and carrying heavy loads, domestic work, sedentary lifestyles, and duration of current employment. A subgroup analysis of the population under study yielded an estimated prevalence of low back pain of 16.7% for the population exposed to a lower number of risk factors and 65% for the higher risk subgroup. In this review, we made an exhaustive search of studies evaluating the epidemiology of chronic low back pain in the Latin America region.Limitations: The large topographic and chronologic variability in definitions of low back pain, interviewer bias, and subject selection bias.Conclusions: Despite the sparse information and the methodological heterogeneity of the studies, pooled results allowed for an indirect estimation of the prevalence of low back pain in the region that was pretty consistent with the published results obtained from other settings. New studies need to be carried out to supplement and overcome the methodological weaknesses of those previously conducted. © 2014, American Society of Interventional Pain Physicians, All rights reserved.